How to run a country : an ancient guide for modern leaders - Cicero, Marcus Tullius (Princeton University Press, 2013)
Marcus Cicero, Rome's greatest statesman and orator, was elected to the Roman Republic's highest office at a time when his beloved country was threatened by power-hungry politicians, dire economic troubles, foreign turmoil, and political parties that refused to work together. Sound familiar? Cicero's letters, speeches, and other writings are filled with timeless wisdom and practical insight about how to solve these and other problems of leadership and politics. How to Run a Country collects the best of these writings to provide an entertaining, common sense guide for modern leaders and citi.